Drip irrigation capillary tube prepared based on modified polyethylene and preparation process
By adding modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate to the drip irrigation capillary material, the problem of insufficient wear resistance and corrosion resistance of existing capillary materials is solved, and the problem of significant Extend service life and improve system efficiency.
Patent Information
- Application Number
- CN202411765900.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During use, existing drip irrigation capillary materials are susceptible to impurities and temperature changes in water, resulting in a decrease in hardness, toughness and chemical corrosion resistance, thereby shortening their service life.
Chemical reagents such as modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate are used to form an anchor bond structure through synergistic effects, which significantly improves the wear resistance and corrosion resistance of the capillary tube.
It significantly improves the wear resistance, heat resistance and corrosion resistance of drip irrigation capillaries, extends service life, reduces system maintenance costs, and improves overall efficiency.
Smart Images

Figure CN119431928A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material application, in particular to a drip irrigation capillary prepared based on modified polyethylene and a preparation process thereof. Background Art
[0002] With the global population growth and increasing environmental pressure, water resources are becoming more and more precious. In the drip irrigation system, the capillary, as the core component of water transmission, is related to the use of the entire drip irrigation system. General capillaries are easily deformed by impurities in the water and outdoor temperature. Long-term use will reduce the service life, resulting in problems such as reduced system flow and capillary damage. The raw material of the capillary is mainly polyethylene. As the use time goes by, the raw material will age, resulting in the hardness, toughness, chemical corrosion resistance, etc. of the capillary being affected. Polymer materials are used to improve the friction resistance and heat resistance of the capillary and increase the service life of the drip irrigation capillary. Polymer materials have excellent physical and chemical properties and are widely used in various fields such as catalysis, medicine, and equipment. Using polymer polyethylene as the material of the drip irrigation capillary can effectively improve the friction resistance and heat resistance of the drip irrigation capillary. Even when the capillary faces temperature changes in different environments and some extreme conditions, it can better maintain its structural integrity and functional stability. Therefore, the use of polymer drip irrigation capillaries not only helps to reduce the maintenance cost of the system, but also improves the overall efficiency of the drip irrigation system, thereby making better use of limited water resources. In addition, polymer drip irrigation capillaries play an important role in the irrigation of fruit trees, vegetables, cash crops, greenhouses, irrigation in arid and water-scarce areas, and water-saving transformation of farmland. Summary of the invention
[0003] (1) Technical issues to be resolved
[0004] The purpose of the present invention is to provide a drip irrigation capillary prepared based on modified polyethylene and a preparation process. By further improving the preparation process, that is, adding chemical reagents such as modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate in the process of preparing the capillary raw materials, the wear resistance of the pipe is significantly improved, and the corrosion resistance is improved to extend the service life, and finally a drip irrigation capillary prepared based on modified polyethylene is obtained.
[0005] (2) Technical solution
[0006] To achieve the above object, the present invention provides a drip irrigation capillary prepared based on modified polyethylene and a preparation process thereof, comprising the following steps:
[0007] Furthermore, the preparation method of the modified ultra-high molecular weight polyethylene comprises:
[0008] S21. Add polyethylene and polypropylene glycol into the first container, the mass ratio of polyethylene to polypropylene glycol is (95-85): (25-15), crush the material in the first container, and then put it into a drying oven, the drying temperature and time are 60-65 ° C and 12-20 h, respectively, to obtain a first composite product;
[0009] S22. The first composite product, SOCl2 and aluminate coupling agent are sequentially added into the second container, wherein the mass ratio of the first composite product, SOCl2 and aluminate coupling agent is (40-55): (5-15): (1.5-2.5), and then the mixture is placed in a stirrer and stirred at 40-50° C. for 8-10 hours, and a second composite product is obtained after the stirring is completed;
[0010] S23. fatty acid ester, dimethyl zirconium and polyvinyl chloride are sequentially added to the second composite product in a mass ratio of (10-30): (1-5): (20-50), and stirring is continued for 4-8 hours. After being fully mixed, a strip-shaped composite is extruded using a twin-screw extruder to obtain a third composite product;
[0011] S24. The third composite product is placed in ice water at -10 to 0°C for cooling, and then freeze-dried at a drying temperature of -25 to -30°C for a drying time of 36 to 48 hours to obtain a modified ultra-high molecular weight polyethylene.
[0012] Furthermore, the density of the modified ultra-high molecular weight polyethylene is 0.927-0.944 g / cm 3 , relative molecular mass is greater than 1 million.
[0013] Furthermore, the preparation method of the modified zirconium phosphate comprises:
[0014] S31. Take zirconium phosphate and tris(hydroxymethyl)aminomethane in a mass ratio of 1:1, dissolved in 500 to 600mL of deionized water, placed in a first container and magnetically stirred, stirring conditions were 1000 to 1200rpm, stirring time was 1 to 3h, to obtain a first mixed solution;
[0015] S32. placing the first mixed solution into an ultrasonic cleaner for ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz for 60 to 100 min, and then standing at room temperature for 24 to 48 h;
[0016] S34. After the static state is completed, centrifuge and elute with deionized water. After eluting 3 to 5 times, place the mixture in a freeze dryer at a drying temperature of -70 to -80°C for 5 to 10 hours to obtain modified zirconium phosphate.
[0017] Furthermore, the modified zirconium phosphate surface was successfully grafted, with a specific surface area of 3000~3800 m 2 / g.
[0018] Furthermore, the mass ratio of the modified ultra-high molecular weight polyethylene to the modified zirconium phosphate is (10-20): (5-10).
[0019] Furthermore, the zinc oxide nanowires are composed of carbon fibers, zinc oxide and lanthanum in a weight ratio of (1-2): (2-3): (3.5-4.5).
[0020] Furthermore, the polymethacrylate is composed of methyl methacrylate, hexacarbonyl chromium and ethyl 2-bromoisobutyrate, in a weight ratio of (1-2): (2-3): (3.5-4.5).
[0021] Furthermore, the E-type glass fiber is composed of Fe2O3, SiO2 and Al2O3, with the weight ratio being (1~2):(2~3):(3.5~4.5).
[0022] On the other hand, based on the same inventive concept, the polymer drip irrigation capillary is prepared by the above-mentioned method for preparing a drip irrigation capillary based on modified polyethylene.
[0023] The mechanism of action of the above raw material components is as follows:
[0024] The raw materials of polymer drip irrigation capillaries are mainly modified ultra-high molecular weight polyethylene, zinc oxide nanowires, modified zirconium phosphate, polymethacrylate and E-type glass fiber. The modified ultra-high molecular weight polyethylene provides excellent wear resistance and corrosion resistance; zinc oxide nanowires enhance the strength and rigidity of the capillary and improve its thermal properties; after surface grafting modification, the modified zirconium phosphate can synergistically increase its wear resistance and corrosion resistance with the modified ultra-high molecular weight polyethylene, and can also be used as an antibacterial agent to prevent microbial contamination in the drip capillary; polymethacrylate is used as the inner wall coating to improve smoothness and corrosion resistance and optimize fluid transmission; E-type glass fiber is used as a reinforcing material to further enhance the overall strength and electrical insulation performance of the capillary.
[0025] The introduction of polymethacrylate can improve the interfacial interaction between modified zirconium phosphate and modified ultra-high molecular weight polyethylene. Polymethacrylate has good compatibility and thermal stability, and the functional groups on its molecular chain can interact with the functional groups on the surface of modified zirconium phosphate, such as hydrogen bonds, van der Waals forces, etc., thereby enhancing the stability of the interface area. At the same time, it can maintain its performance in a high temperature environment and prevent it from corroding or degrading in certain chemical environments. This helps to improve the chemical resistance of the composite material. E-type glass fiber has high strength, high modulus and good chemical stability, and its surface is usually specially treated to enhance the bonding force with the polymer matrix. When E-type glass fiber is introduced as a reinforcing phase into a composite material of modified zirconium phosphate, modified ultra-high molecular weight polyethylene and zinc oxide nanowires, an effective physical and chemical bond can be formed between its fiber surface and the three modified materials. And the stress distribution of the entire composite material can be optimized. This improvement in stress distribution helps to reduce the stress concentration phenomenon of the composite material during the stress process and improve the fatigue resistance and durability of the composite material.
[0026] In the preparation of polymer drip irrigation capillaries, modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate play a role through synergistic effects, and an effective anchoring and bonding structure is formed between modified zirconium phosphate and modified ultra-high molecular weight polyethylene. Modified ultra-high molecular weight polyethylene is a polymer material. By adding an aluminate coupling agent, effective surface grafting can be achieved while fully retaining the unique mechanical properties of polyethylene. Modified zirconium phosphate is modified by grafting the surface of tris(hydroxymethyl)aminomethane crystals, so that it can not only have hydrogen bonding between surface vinyltriethoxysilane molecular chains and anchoring and bonding structures with modified ultra-high molecular weight polyethylene molecules. Zinc oxide nanowires are evenly dispersed inside the modified ultra-high molecular weight polyethylene, forming an interlaced network structure with the modified ultra-high molecular weight polyethylene molecules. When affected by external temperature, the movement of the modified ultra-high molecular weight polyethylene molecular chains is hindered, which improves the high temperature resistance of the composite material. The anchoring and bonding structure between modified zirconium phosphate and modified ultra-high molecular weight polyethylene is enhanced, effectively preventing the thermal movement of the modified ultra-high molecular weight polyethylene molecular chains and increasing the thermal deformation temperature of the material. Improve the processing of modified ultra-high molecular weight polyethylene plastics to disentangle and improve the high temperature resistance of composite materials. After zinc oxide nanowires are added to the system, the unique hexagonal wurtzite structure of the nanomaterial can synergize the crystallization of modified zirconium phosphate and modified ultra-high molecular weight polyethylene, which not only effectively improves the wear resistance of the material, but also improves the corrosion resistance and high temperature resistance of the material.
[0027] (3) Beneficial effects
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. Modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate play a role through synergistic effect, forming an anchoring bonding structure, improving interface interaction, and assisted by silane coupling agent to construct an inorganic-organic composite structure. Then, the zinc oxide nanowires are strengthened and connected through the hollow structure to enhance the overall combination of the two, significantly improving the heat resistance and corrosion resistance of the composite material;
[0030] 2. Modified ultra-high molecular weight polyethylene has the characteristics of low friction and high wear resistance. The surface grafted polymer brush layer can effectively improve the friction performance. The method of adding aluminate coupling agent can effectively carry out surface grafting, reduce the extrusion deformation, tearing and grinding of the friction surface of the composite material, and reduce the wear of the composite material;
[0031] 3. Modified zirconium phosphate has good chemical reactivity, and its performance can be improved by intercalation modification and other methods. Vinyl triethoxysilane, as an important silane coupling agent, is used to carry out surface grafting modification on modified zirconium phosphate, and the anchoring bonding structure formed with the surface groups of modified ultra-high molecular weight polyethylene is effectively combined with the modified ultra-high molecular weight polyethylene to improve the wear resistance and corrosion resistance of the material.
[0032] 4. The hexagonal wurtzite structure of zinc oxide nanowires can achieve uniform and stable dispersion inside the modified ultra-high molecular weight polyethylene plastic, so that the modified ultra-high molecular weight polyethylene molecular chains form an intricate interlaced network structure, which can better promote the anchoring and bonding structure formed by the modified zirconium phosphate and the surface groups of the modified ultra-high molecular weight polyethylene, effectively maintain the polymer dropper capillary to show stronger durability during friction and wear, and increase corrosion resistance and high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the SEM image of the modified ultra-high molecular weight polyethylene of Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The experimental equipment and preparations of the embodiments described below are as follows: electronic balance (Sartorius, Germany), magnetic stirrer (Meiyingpu, Shanghai), high-speed centrifuge (Guangzhou Jidi), freeze dryer (Shanghai Pudong Freeze Drying), vacuum drying oven (Shanghai Jiecheng), high-speed pulverizer (Shandong Tianfang Machinery), pH meter (Shanghai Yidian), oscillator (Shanghai Analyzer), scanning electron microscope (Zeiss, Germany), specific surface area analyzer (Beijing Best), JSH-65 twin-screw extruder (Cotton Asia Machinery), shrink film (Shanghai Heguan); PE, PC (Shanghai Chemical Research Institute Co., Ltd.), zirconium phosphate (Zhongshan Dixin Chemical Co., Ltd.); chemicals and reagents were purchased from Sigma-Aldrich.
[0036] Example 1: This example discloses a method for preparing a drip irrigation capillary based on modified polyethylene, comprising the following steps:
[0037] S11. The prepared modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate are sequentially placed in a blender, wherein the mass ratio of the modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate is 15:6:5, and mixed evenly in a high-speed mode to obtain a first composite material;
[0038] S12. Under stirring, sequentially adding the first composite material, polymethacrylate and E-type glass fiber to the first container, the mass ratio of the first composite material, polymethacrylate and E-type glass fiber being 5:1:0.5, to obtain a second composite material;
[0039] S13. placing the second composite material in an internal mixer, mixing at 180-190°C and 40-50 r / min for 10 min, and then pressurizing at 190°C with a pressure of 3 MPa for 6 min to obtain a third composite material;
[0040] S14. The third composite material is placed on a shrink film by a shrink mold method, and low-temperature molding is performed at a speed of 50 to 70 rpm at a temperature of 30 to 40 °C;
[0041] S15. Use immersion cooling at 40℃~50℃, with the water surface 10~20mm higher than the pipe, and then place it in freeze drying, with the freezing temperature of -5~0℃ and the freezing time of 1~5h. After demolding, the polymer drip irrigation capillary is obtained.
[0042] The preparation method of the modified ultra-high molecular weight polyethylene comprises:
[0043] S21. Add polyethylene and polypropylene glycol into the first container, the mass ratio of polyethylene to polypropylene glycol is 85:20, crush the material in the first container, and then put it into a drying oven, the drying temperature and time are 60-65 ° C and 12-20 h, respectively, to obtain a first composite product;
[0044] S22. In a second container, the first composite product, SOCl2 and an aluminate coupling agent are added in sequence, wherein the mass ratio of the first composite product, SOCl2 and the aluminate coupling agent is 40:5:1.5, and then the mixture is placed in a stirrer and stirred at 40-50° C. for 8-10 hours, and after the stirring is completed, a second composite product is obtained;
[0045] S23. fatty acid ester, dimethyl zirconium and polyvinyl chloride are sequentially added to the second composite product in a mass ratio of 10:1:20, and stirring is continued for 4 to 8 hours. After being fully mixed, a strip-shaped composite is extruded using a twin-screw extruder to obtain a third composite product;
[0046] S24. The third composite product is placed in ice water at -10 to 0°C for cooling, and then freeze-dried at a drying temperature of -25 to -30°C for a drying time of 36 to 48 hours to obtain a modified ultra-high molecular weight polyethylene.
[0047] The density of the modified ultra-high molecular weight polyethylene is 0.927-0.944 g / cm 3 , relative molecular mass is greater than 1 million.
[0048] The preparation method of the modified zirconium phosphate comprises:
[0049] S31. Take zirconium phosphate and tris(hydroxymethyl)aminomethane in a mass ratio of 1:1, dissolved in 500 to 600mL of deionized water, placed in a first container and magnetically stirred, stirring conditions were 1000 to 1200rpm, stirring time was 1 to 3h, to obtain a first mixed solution;
[0050] S32. placing the first mixed solution into an ultrasonic cleaner for ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz for 60 to 100 min, and then standing at room temperature for 24 to 48 h;
[0051] S34. After the static state is completed, centrifuge and elute with deionized water. After eluting 3 to 5 times, place the mixture in a freeze dryer at a drying temperature of -70 to -80°C for 5 to 10 hours to obtain modified zirconium phosphate.
[0052] The modified zirconium phosphate surface was successfully grafted, with a specific surface area of 3000~3800 m 2 / g.
[0053] The zinc oxide nanowires are composed of carbon fibers, zinc oxide and lanthanum in a weight ratio of 1:2:3.5.
[0054] The polymethacrylate is composed of methyl methacrylate, hexacarbonyl chromium and ethyl 2-bromoisobutyrate in a weight ratio of 1:2:3.5.
[0055] The E-type glass fiber is composed of Fe2O3, SiO2 and Al2O3 in a weight ratio of 1:2:3.5.
[0056] In the preparation process of polymer drip irrigation capillaries, modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate play a role through synergistic effect. The modified ultra-high molecular weight polyethylene is added with silane coupling agent, and the wear resistance and poor heat resistance can be effectively improved by cross-linking. Figure 1 The SEM image of the modified ultra-high molecular weight polyethylene shown in the figure shows that the modified ultra-high molecular weight polyethylene is added with a silane coupling agent, and obvious gaps appear, and the stacking degree is weakened, and the fiber is more dispersed. In the preparation process, the modified zirconium phosphate is introduced, and vinyl triethoxysilane is added to the zirconium phosphate, and the surface is grafted and modified, which effectively promotes the compatibility of the modified zirconium phosphate and the modified ultra-high molecular weight polyethylene molecular chain. The vinyl triethoxysilane coupling agent molecules in the modified zirconium phosphate play a molecular bridge role, forming an inorganic phase / silane coupling agent / organic phase bonding state, improving the interface interaction with the modified ultra-high molecular weight polyethylene matrix, and firmly connecting the modified zirconium phosphate and the modified ultra-high molecular weight polyethylene. The anchoring bonding structure formed by the surface group of the modified ultra-high molecular weight polyethylene effectively combines with the modified ultra-high molecular weight polyethylene, and improves the wear resistance and corrosion resistance of the material. However, the addition of modified zirconium phosphate can also reduce the deformation and tearing of the composite surface, making the composite material easy to agglomerate, and it is difficult to maintain the anchoring bonding structure. Therefore, zinc oxide nanowires with hollow structures are added. The zinc oxide nanowires can form an interlaced network structure with modified ultra-high molecular weight polyethylene molecules, effectively strengthening the anchoring and bonding structure of modified ultra-high molecular weight polyethylene and modified zirconium phosphate, enabling it to better maintain wear resistance, while effectively increasing high temperature resistance and corrosion resistance. The introduction of polymethacrylate can improve the interfacial interaction between modified zirconium phosphate and modified ultra-high molecular weight polyethylene. The functional groups on its molecular chain can interact with the functional groups on the surface of modified zirconium phosphate, such as hydrogen bonds, van der Waals forces, etc., thereby enhancing the stability of the interface area. E-type glass fiber can enhance the overall bonding strength with the polymer matrix.
[0057] Example 2: This example discloses a method for preparing a drip irrigation capillary based on modified polyethylene, comprising the following steps:
[0058] S11. The prepared modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate are sequentially placed in a blender, wherein the mass ratio of the modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate is 10:6:5, and mixed evenly in a high-speed mode to obtain a first composite material;
[0059] S12. Under stirring, sequentially adding the first composite material, polymethacrylate and E-type glass fiber to the first container, the mass ratio of the first composite material, polymethacrylate and E-type glass fiber being 5:1:0.5, to obtain a second composite material;
[0060] S13. placing the second composite material in an internal mixer, mixing at 180-190°C and 40-50 r / min for 10 min, and then pressurizing at 190°C with a pressure of 3 MPa for 6 min to obtain a third composite material;
[0061] S14. The third composite material is placed on a shrink film by a shrink mold method, and low-temperature molding is performed at a speed of 50 to 70 rpm at a temperature of 30 to 40 °C;
[0062] S15. Use immersion cooling at 40℃~50℃, with the water surface 10~20mm higher than the pipe, and then place it in freeze drying, with the freezing temperature of -5~0℃ and the freezing time of 1~5h. After demolding, the polymer drip irrigation capillary is obtained.
[0063] The preparation method of the modified ultra-high molecular weight polyethylene comprises:
[0064] S21. Add polyethylene and polypropylene glycol into the first container, the mass ratio of polyethylene to polypropylene glycol is 85:20, crush the material in the first container, and then put it into a drying oven, the drying temperature and time are 60-65 ° C and 12-20 h, respectively, to obtain a first composite product;
[0065] S22. In a second container, the first composite product, SOCl2 and an aluminate coupling agent are added in sequence, wherein the mass ratio of the first composite product, SOCl2 and the aluminate coupling agent is 40:5:1.5, and then the mixture is placed in a stirrer and stirred at 40-50° C. for 8-10 hours, and after the stirring is completed, a second composite product is obtained;
[0066] S23. fatty acid ester, dimethyl zirconium and polyvinyl chloride are sequentially added to the second composite product in a mass ratio of 10:1:20, and stirring is continued for 4 to 8 hours. After being fully mixed, a strip-shaped composite is extruded using a twin-screw extruder to obtain a third composite product;
[0067] S24. The third composite product is placed in ice water at -10 to 0°C for cooling, and then freeze-dried at a drying temperature of -25 to -30°C for a drying time of 36 to 48 hours to obtain a modified ultra-high molecular weight polyethylene.
[0068] The density of the modified ultra-high molecular weight polyethylene is 0.927-0.944 g / cm 3 , relative molecular mass is greater than 1 million.
[0069] The preparation method of the modified zirconium phosphate comprises:
[0070] S31. Take zirconium phosphate and tris(hydroxymethyl)aminomethane in a mass ratio of 1:1, dissolved in 500 to 600mL of deionized water, placed in a first container and magnetically stirred, stirring conditions were 1000 to 1200rpm, stirring time was 1 to 3h, to obtain a first mixed solution;
[0071] S32. placing the first mixed solution into an ultrasonic cleaner for ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz for 60 to 100 min, and then standing at room temperature for 24 to 48 h;
[0072] S34. After the static state is completed, centrifuge and elute with deionized water. After eluting 3 to 5 times, place the mixture in a freeze dryer at a drying temperature of -70 to -80°C for 5 to 10 hours to obtain modified zirconium phosphate.
[0073] The modified zirconium phosphate surface was successfully grafted, with a specific surface area of 3000~3800 m 2 / g.
[0074] The zinc oxide nanowires are composed of carbon fibers, zinc oxide and lanthanum in a weight ratio of 1:2:3.5.
[0075] The polymethacrylate is composed of methyl methacrylate, hexacarbonyl chromium and ethyl 2-bromoisobutyrate in a weight ratio of 1:2:3.5.
[0076] The E-type glass fiber is composed of Fe2O3, SiO2 and Al2O3 in a weight ratio of 1:2:3.5.
[0077] Example 3: This example discloses a method for preparing a drip irrigation capillary based on modified polyethylene, comprising the following steps:
[0078] S11. The prepared modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate are sequentially placed in a blender, wherein the mass ratio of the modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate is 20:6:5, and mixed evenly in a high-speed mode to obtain a first composite material;
[0079] S12. Under stirring, sequentially adding the first composite material, polymethacrylate and E-type glass fiber to the first container, the mass ratio of the first composite material, polymethacrylate and E-type glass fiber being 5:1:0.5, to obtain a second composite material;
[0080] S13. placing the second composite material in an internal mixer, mixing at 180-190°C and 40-50 r / min for 10 min, and then pressurizing at 190°C with a pressure of 3 MPa for 6 min to obtain a third composite material;
[0081] S14. The third composite material is placed on a shrink film by a shrink mold method, and low-temperature molding is performed at a speed of 50 to 70 rpm at a temperature of 30 to 40 °C;
[0082] S15. Use immersion cooling at 40℃~50℃, with the water surface 10~20mm higher than the pipe, and then place it in freeze drying, with the freezing temperature of -5~0℃ and the freezing time of 1~5h. After demolding, the polymer drip irrigation capillary is obtained.
[0083] The preparation method of the modified ultra-high molecular weight polyethylene comprises:
[0084] S21. Add polyethylene and polypropylene glycol into the first container, the mass ratio of polyethylene to polypropylene glycol is 85:20, crush the material in the first container, and then put it into a drying oven, the drying temperature and time are 60-65 ° C and 12-20 h, respectively, to obtain a first composite product;
[0085] S22. In a second container, the first composite product, SOCl2 and an aluminate coupling agent are added in sequence, wherein the mass ratio of the first composite product, SOCl2 and the aluminate coupling agent is 40:5:1.5, and then the mixture is placed in a stirrer and stirred at 40-50° C. for 8-10 hours, and after the stirring is completed, a second composite product is obtained;
[0086] S23. fatty acid ester, dimethyl zirconium and polyvinyl chloride are sequentially added to the second composite product in a mass ratio of 10:1:20, and stirring is continued for 4 to 8 hours. After being fully mixed, a strip-shaped composite is extruded using a twin-screw extruder to obtain a third composite product;
[0087] S24. The third composite product is placed in ice water at -10 to 0°C for cooling, and then freeze-dried at a drying temperature of -25 to -30°C for a drying time of 36 to 48 hours to obtain a modified ultra-high molecular weight polyethylene.
[0088] The density of the modified ultra-high molecular weight polyethylene is 0.927-0.944 g / cm 3, relative molecular mass is greater than 1 million.
[0089] The preparation method of the modified zirconium phosphate comprises:
[0090] S31. Take zirconium phosphate and tris(hydroxymethyl)aminomethane in a mass ratio of 1:1, dissolved in 500 to 600mL of deionized water, placed in a first container and magnetically stirred, stirring conditions were 1000 to 1200rpm, stirring time was 1 to 3h, to obtain a first mixed solution;
[0091] S32. placing the first mixed solution into an ultrasonic cleaner for ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz for 60 to 100 min, and then standing at room temperature for 24 to 48 h;
[0092] S34. After the static state is completed, centrifuge and elute with deionized water. After eluting 3 to 5 times, place the mixture in a freeze dryer at a drying temperature of -70 to -80°C for 5 to 10 hours to obtain modified zirconium phosphate.
[0093] The modified zirconium phosphate surface was successfully grafted, with a specific surface area of 3000~3800 m 2 / g.
[0094] The zinc oxide nanowires are composed of carbon fibers, zinc oxide and lanthanum in a weight ratio of 1:2:3.5.
[0095] The polymethacrylate is composed of methyl methacrylate, hexacarbonyl chromium and ethyl 2-bromoisobutyrate in a weight ratio of 1:2:3.5.
[0096] The E-type glass fiber is composed of Fe2O3, SiO2 and Al2O3 in a weight ratio of 1:2:3.5.
[0097] Example 4: This example discloses a method for preparing a drip irrigation capillary based on modified polyethylene, comprising the following steps:
[0098] S11. The prepared modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate are sequentially placed in a blender, wherein the mass ratio of the modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate is 15:9:5, and mixed evenly in a high-speed mode to obtain a first composite material;
[0099] S12. Under stirring, sequentially adding the first composite material, polymethacrylate and E-type glass fiber to the first container, the mass ratio of the first composite material, polymethacrylate and E-type glass fiber being 5:1:0.5, to obtain a second composite material;
[0100] S13. placing the second composite material in an internal mixer, mixing at 180-190°C and 40-50 r / min for 10 min, and then pressurizing at 190°C with a pressure of 3 MPa for 6 min to obtain a third composite material;
[0101] S14. The third composite material is placed on a shrink film by a shrink mold method, and low-temperature molding is performed at a speed of 50 to 70 rpm at a temperature of 30 to 40 °C;
[0102] S15. Use immersion cooling at 40℃~50℃, with the water surface 10~20mm higher than the pipe, and then place it in freeze drying, with the freezing temperature of -5~0℃ and the freezing time of 1~5h. After demolding, the polymer drip irrigation capillary is obtained.
[0103] The preparation method of the modified ultra-high molecular weight polyethylene comprises:
[0104] S21. Add polyethylene and polypropylene glycol into the first container, the mass ratio of polyethylene to polypropylene glycol is 85:20, crush the material in the first container, and then put it into a drying oven, the drying temperature and time are 60-65 ° C and 12-20 h, respectively, to obtain a first composite product;
[0105] S22. In a second container, the first composite product, SOCl2 and an aluminate coupling agent are added in sequence, wherein the mass ratio of the first composite product, SOCl2 and the aluminate coupling agent is 40:5:1.5, and then the mixture is placed in a stirrer and stirred at 40-50° C. for 8-10 hours, and after the stirring is completed, a second composite product is obtained;
[0106] S23. fatty acid ester, dimethyl zirconium and polyvinyl chloride are sequentially added to the second composite product in a mass ratio of 10:1:20, and stirring is continued for 4 to 8 hours. After being fully mixed, a strip-shaped composite is extruded using a twin-screw extruder to obtain a third composite product;
[0107] S24. The third composite product is placed in ice water at -10 to 0°C for cooling, and then freeze-dried at a drying temperature of -25 to -30°C for a drying time of 36 to 48 hours to obtain a modified ultra-high molecular weight polyethylene.
[0108] The density of the modified ultra-high molecular weight polyethylene is 0.927-0.944 g / cm 3 , relative molecular mass is greater than 1 million.
[0109] The preparation method of the modified zirconium phosphate comprises:
[0110] S31. Take zirconium phosphate and tris(hydroxymethyl)aminomethane in a mass ratio of 1:1, dissolved in 500 to 600mL of deionized water, placed in a first container and magnetically stirred, stirring conditions were 1000 to 1200rpm, stirring time was 1 to 3h, to obtain a first mixed solution;
[0111] S32. placing the first mixed solution into an ultrasonic cleaner for ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz for 60 to 100 min, and then standing at room temperature for 24 to 48 h;
[0112] S34. After the static state is completed, centrifuge and elute with deionized water. After eluting 3 to 5 times, place the mixture in a freeze dryer at a drying temperature of -70 to -80°C for 5 to 10 hours to obtain modified zirconium phosphate.
[0113] The modified zirconium phosphate surface was successfully grafted, with a specific surface area of 3000~3800 m 2 / g.
[0114] The zinc oxide nanowires are composed of carbon fibers, zinc oxide and lanthanum in a weight ratio of 1:2:3.5.
[0115] The polymethacrylate is composed of methyl methacrylate, hexacarbonyl chromium and ethyl 2-bromoisobutyrate in a weight ratio of 1:2:3.5.
[0116] The E-type glass fiber is composed of Fe2O3, SiO2 and Al2O3 in a weight ratio of 1:2:3.5.
[0117] Example 5: This example discloses a method for preparing a drip irrigation capillary based on modified polyethylene, comprising the following steps:
[0118] S11. The prepared modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate are sequentially placed in a blender, wherein the mass ratio of the modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate is 15:6:10, and mixed evenly in a high-speed mode to obtain a first composite material;
[0119] S12. Under stirring, sequentially adding the first composite material, polymethacrylate and E-type glass fiber to the first container, the mass ratio of the first composite material, polymethacrylate and E-type glass fiber being 5:1:0.5, to obtain a second composite material;
[0120] S13. placing the second composite material in an internal mixer, mixing at 180-190°C and 40-50 r / min for 10 min, and then pressurizing at 190°C with a pressure of 3 MPa for 6 min to obtain a third composite material;
[0121] S14. The third composite material is placed on a shrink film by a shrink mold method, and low-temperature molding is performed at a speed of 50 to 70 rpm at a temperature of 30 to 40 °C;
[0122] S15. Use immersion cooling at 40℃~50℃, with the water surface 10~20mm higher than the pipe, and then place it in freeze drying, with the freezing temperature of -5~0℃ and the freezing time of 1~5h. After demolding, the polymer drip irrigation capillary is obtained.
[0123] The preparation method of the modified ultra-high molecular weight polyethylene comprises:
[0124] S21. Add polyethylene and polypropylene glycol into the first container, the mass ratio of polyethylene to polypropylene glycol is 85:20, crush the material in the first container, and then put it into a drying oven, the drying temperature and time are 60-65 ° C and 12-20 h, respectively, to obtain a first composite product;
[0125] S22. In a second container, the first composite product, SOCl2 and an aluminate coupling agent are added in sequence, wherein the mass ratio of the first composite product, SOCl2 and the aluminate coupling agent is 40:5:1.5, and then the mixture is placed in a stirrer and stirred at 40-50° C. for 8-10 hours, and after the stirring is completed, a second composite product is obtained;
[0126] S23. fatty acid ester, dimethyl zirconium and polyvinyl chloride are sequentially added to the second composite product in a mass ratio of 10:1:20, and stirring is continued for 4 to 8 hours. After being fully mixed, a strip-shaped composite is extruded using a twin-screw extruder to obtain a third composite product;
[0127] S24. The third composite product is placed in ice water at -10 to 0°C for cooling, and then freeze-dried at a drying temperature of -25 to -30°C for a drying time of 36 to 48 hours to obtain a modified ultra-high molecular weight polyethylene.
[0128] The density of the modified ultra-high molecular weight polyethylene is 0.927-0.944 g / cm 3 , relative molecular mass is greater than 1 million.
[0129] The preparation method of the modified zirconium phosphate comprises:
[0130] S31. Take zirconium phosphate and tris(hydroxymethyl)aminomethane in a mass ratio of 1:1, dissolved in 500 to 600mL of deionized water, placed in a first container and magnetically stirred, stirring conditions were 1000 to 1200rpm, stirring time was 1 to 3h, to obtain a first mixed solution;
[0131] S32. placing the first mixed solution into an ultrasonic cleaner for ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz for 60 to 100 min, and then standing at room temperature for 24 to 48 h;
[0132] S34. After the static state is completed, centrifuge and elute with deionized water. After eluting 3 to 5 times, place the mixture in a freeze dryer at a drying temperature of -70 to -80°C for 5 to 10 hours to obtain modified zirconium phosphate.
[0133] The modified zirconium phosphate surface was successfully grafted, with a specific surface area of 3000~3800 m 2 / g.
[0134] The zinc oxide nanowires are composed of carbon fibers, zinc oxide and lanthanum in a weight ratio of 1:2:3.5.
[0135] The polymethacrylate is composed of methyl methacrylate, hexacarbonyl chromium and ethyl 2-bromoisobutyrate in a weight ratio of 1:2:3.5.
[0136] The E-type glass fiber is composed of Fe2O3, SiO2 and Al2O3 in a weight ratio of 1:2:3.5.
[0137] Control group 1: This embodiment differs from embodiment 1 in that modified ultra-high molecular weight polyethylene is not contained. The method for preparing a drip irrigation capillary based on modified polyethylene in this embodiment is consistent with that in embodiment 1.
[0138] Control group 2: This example differs from example 1 in that modified zirconium phosphate is not contained. The method for preparing a drip irrigation capillary based on modified polyethylene in this example is consistent with that in example 1.
[0139] Control group 3: This embodiment differs from embodiment 1 in that zinc oxide nanowires are not included. The method for preparing a drip irrigation capillary based on modified polyethylene in this embodiment is consistent with that in embodiment 1.
[0140] Control group 4: This example differs from Example 1 in that the modified ultra-high molecular weight polyethylene is not included, and the modified ultra-high molecular weight polyethylene is replaced by polyethylene. The method for preparing a drip irrigation capillary based on modified polyethylene in this example is consistent with that in Example 1.
[0141] Control group 5: This example differs from Example 1 in that the modified zirconium phosphate is not included, and the modified zirconium phosphate is replaced by zirconium phosphate. The method for preparing a drip irrigation capillary based on modified polyethylene in this example is consistent with that in Example 1.
[0142] Effect evaluation: Analysis of friction, wear and high temperature resistance of polymer drip irrigation capillaries: Five polymer drip irrigation capillaries prepared in each experimental group were randomly selected and subjected to friction and wear tests using a friction and wear tester. The test was carried out under indoor atmospheric conditions, and each sample was tested three times under the same conditions. After the friction and wear test, a white light interferometer was used to observe the wear scar morphology on the sample surface and calculate the wear volume. The wear volume was taken as the average of the three statistical results. EDS was used to analyze the elemental composition of the wear scar surface. The formula for the wear rate is as follows:
[0143]
[0144] Note: W is the wear rate, unit: mm 3 / (N·m); V is the wear volume: unit: mm 3 ; N is the loading force, unit: N; S is the total stroke length, unit: m.
[0145] The friction coefficient formula is as follows:
[0146]
[0147] Note: μ is the friction coefficient; F is the friction force: unit: N; W is the vertical force: unit: N.
[0148] The heat resistance of the experimental materials was tested in accordance with the national standard GB / T 1634.1-2018, and the average value was taken and the measurement results were recorded.
[0149] Table 1 Statistical results of friction and wear performance of polymer drip irrigation capillaries in each experimental group
[0150] sample Friction coefficient <![CDATA[Wear rate (mm 3 / (N·m))]]> Example 1 0.189 <![CDATA[4.598×10 -6 ]]> Example 2 0.210 <![CDATA[6.876×10 -6 ]]> Example 3 0.265 <![CDATA[5.362×10 -6 ]]> Example 4 0.271 <![CDATA[5.211×10 -6 ]]> Example 5 0.278 <![CDATA[5.362×10 -6 ]]> Control group 1 0.543 <![CDATA[9.462×10 -6 ]]> Control group 2 0.761 <![CDATA[8.221×10 -6 ]]> Control group 3 0.559 <![CDATA[9.375×10 -6 ]]> Control group 4 0.498 <![CDATA[8.375×10 -6 ]]> Control group 5 0.421 <![CDATA[9.314×10 -6 ]]>
[0151] Table 1 shows the statistical results of the friction and wear measurement of the polymer drip irrigation capillary. It can be seen from Table 1 that there are certain differences in the proportions of the raw materials of the polymer drip irrigation capillary in each experimental group. By comparing the friction and wear of the polymer drip irrigation capillary prepared in Examples 1 to 5 with those in Control Groups 1 to 5, it can be found that, overall, the friction rate of the polymer drip irrigation capillary prepared in Examples 1 to 5 is higher, indicating that the modified drip irrigation capillary effectively improves the friction resistance, and the friction coefficient and wear rate of the polymer drip irrigation capillary prepared in Example 1 are significantly the lowest, which are 0.189 and 5.362×10 -6 mm 3 / (N·m), and the wear scar is the shallowest.
[0152] Table 2 Statistical results of high temperature resistance of polymer drip irrigation capillaries in each experimental group
[0153] sample Heat deformation temperature (℃) Morphological changes Example 1 126 No deformation at around 100℃ Example 2 110 Slight deformation begins at around 100°C Example 3 113 Slight deformation begins at around 101°C Example 4 117 Slight deformation begins at around 106°C Example 5 109 Slight deformation begins at around 100°C Control group 1 60 Slight deformation begins at around 50°C Control group 2 85 Slight deformation begins at around 80°C Control group 3 89 Slight deformation begins at around 82°C Control group 4 99 Slight deformation begins at around 90°C Control group 5 94 Slight deformation begins at around 90°C
[0154] As can be seen from Table 2, there are certain differences in the proportions of raw materials of polymer drip irrigation capillaries in each experimental group. By comparing the heat resistance of the polymer drip irrigation capillaries prepared in Examples 1 to 5 with that in Control Groups 1 to 5, it can be found that, overall, the heat resistance of the polymer drip irrigation capillaries prepared in Examples 1 to 5 is good, and the value of the heat deformation temperature of the polymer drip irrigation capillaries prepared in Example 1 is obviously the highest, up to 126°C, and the degree of deformation is small. This shows that the synergistic effect of modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate plays a great role, and the anchoring and bonding structure between modified zirconium phosphate and modified ultra-high molecular weight polyethylene can increase the wear resistance of the polymer drip irrigation capillaries. After further adding zinc oxide nanowires, the overall stability of the anchoring and bonding structure is maintained, and the heat resistance of the polymer drip irrigation capillaries is also improved. By comparing the polymer drip irrigation capillary prepared in Example 1 with the control groups 1 to 5, it can be found that the differences in friction, wear and high temperature resistance are very obvious, which shows that when adding modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate at the same time in the process of preparing the polymer drip irrigation capillary, the practical value of the polymer drip irrigation capillary can be significantly improved.
[0155] Through the above limited experiments, the drip irrigation capillary material prepared based on modified polyethylene in Example 1 of the present invention has significant effect. By optimizing the preparation method of the polymer drip irrigation capillary raw material, modified ultra-high molecular weight polyethylene and modified zirconium phosphate and other chemical additives are added in the process of preparing the polymer drip irrigation capillary, the anchoring and bonding structure stability in the composite material is significantly improved, and the overall wear resistance and heat resistance of the drip irrigation capillary are improved. Finally, a high-quality polymer drip irrigation capillary raw material is obtained. The obtained polymer drip irrigation capillary raw material has great application potential. The polymer drip irrigation capillary raw material can be applied to agriculture, chemical industry and other fields to achieve large-scale production, thereby promoting the healthy and orderly development of the industry.
[0156] Finally, it should be noted that: Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a drip irrigation capillary based on modified polyethylene, characterized in that: The following steps are involved: S11. sequentially placing the prepared modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate into a blender, wherein the mass ratio of the modified ultra-high molecular weight polyethylene, zinc oxide nanowires and modified zirconium phosphate is (10-20): (6-9): (5-10), and uniformly mixing them in a high-speed mode to obtain a first composite material; S12. Under stirring, sequentially adding the first composite material, polymethacrylate and E-type glass fiber to the first container, wherein the mass ratio of the first composite material, polymethacrylate and E-type glass fiber is (5-8): (1-3): (0.5-1.5), to obtain a second composite material; S13. placing the second composite material in an internal mixer, mixing it at 180-190°C and 40-50 r / min for 10 min, and then pressurizing it at 190-200°C with a pressure of 3-4 MPa for 6-10 min to obtain a third composite material; S14. The third composite material is placed on a shrink film by a shrink mold method, and low-temperature molding is performed at a speed of 50 to 70 rpm at a temperature of 30 to 40 °C; S15. Use immersion cooling at 40℃~50℃, with the water surface 10~20mm higher than the pipe, and then place it in freeze drying, with the freezing temperature of -5~0℃ and the freezing time of 1~5h. After demolding, the polymer drip irrigation capillary is obtained.
2. The method for preparing a drip irrigation capillary based on modified polyethylene according to claim 1, characterized in that: The preparation method of the modified ultra-high molecular weight polyethylene comprises: S21. Add polyethylene and polypropylene glycol into a first container, wherein the mass ratio of polyethylene to polypropylene glycol is (95-85):(25-15), crush the material in the first container, and then place it in a drying oven at a drying temperature and time of 60-65° C. and 12-20 h, respectively, to obtain a first composite product; S22. The first composite product, SOCl2 and aluminate coupling agent are sequentially added into the second container, wherein the mass ratio of the first composite product, SOCl2 and aluminate coupling agent is (40-55): (5-15): (1.5-2.5), and then the mixture is placed in a stirrer and stirred at 40-50° C. for 8-10 hours, and a second composite product is obtained after the stirring is completed; S23. fatty acid ester, dimethyl zirconium and polyvinyl chloride are sequentially added to the second composite product in a mass ratio of (10-30): (1-5): (20-50), and stirring is continued for 4-8 hours. After being fully mixed, a strip-shaped composite is extruded using a twin-screw extruder to obtain a third composite product; S24. The third composite product is placed in ice water at -10 to 0°C for cooling, and then freeze-dried at a drying temperature of -25 to -30°C for a drying time of 36 to 48 hours to obtain a modified ultra-high molecular weight polyethylene.
3. The method for preparing a drip irrigation capillary based on modified polyethylene according to claim 2, characterized in that: The density of the modified ultra-high molecular weight polyethylene is 0.927-0.944 g / cm 3 , relative molecular mass is greater than 1 million.
4. The method for preparing a drip irrigation capillary based on modified polyethylene according to claim 1, characterized in that: The preparation method of the modified zirconium phosphate comprises: S31. Take zirconium phosphate and tris(hydroxymethyl)aminomethane in a mass ratio of 1:1, dissolved in 500 to 600mL of deionized water, placed in a first container and magnetically stirred, stirring conditions were 1000 to 1200rpm, stirring time was 1 to 3h, to obtain a first mixed solution; S32. placing the first mixed solution into an ultrasonic cleaner for ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz for 60 to 100 min, and then standing at room temperature for 24 to 48 h; S34. After the static state is completed, centrifuge and elute with deionized water. After eluting 3 to 5 times, place the mixture in a freeze dryer at a drying temperature of -70 to -80°C for 5 to 10 hours to obtain modified zirconium phosphate.
5. The method for preparing a drip irrigation capillary based on modified polyethylene according to claim 4, characterized in that: The modified zirconium phosphate surface was successfully grafted, with a specific surface area of 3000~3800 m 2 / g.
6. The method for preparing a drip irrigation capillary based on modified polyethylene according to claim 1, characterized in that: The mass ratio of the modified ultra-high molecular weight polyethylene to the modified zirconium phosphate is (10-20): (5-10).
7. The method for preparing a drip irrigation capillary based on modified polyethylene according to claim 1, characterized in that: The zinc oxide nanowires are composed of carbon fibers, zinc oxide and lanthanum in a weight ratio of (1-2): (2-3): (3.5-4.5).
8. The method for preparing a drip irrigation capillary based on modified polyethylene according to claim 1, characterized in that: The polymethacrylate is composed of methyl methacrylate, hexacarbonyl chromium and ethyl 2-bromoisobutyrate in a weight ratio of (1-2): (2-3): (3.5-4.5).
9. The method for preparing a drip irrigation capillary based on modified polyethylene according to claim 1, characterized in that: The E-type glass fiber is composed of Fe2O3, SiO2 and Al2O3, with the weight ratio being (1-2): (2-3): (3.5-4.5).
10. A drip irrigation capillary made from modified polyethylene, characterized in that: The polymer drip irrigation capillary is prepared by the method for preparing a drip irrigation capillary based on modified polyethylene as described in any one of claims 1 to 9.